Is coaches` perceived team performance associated with their intentions to persist in coaching? The mediating role of coaches` psychological needs and motivation - Pulido, J. J.; van Puyenbroeck, S.; López-Gajardo, M. Á.; Broek, G. V.; Leo, M. F. (Journal of Sports Sciences, 2023)
This study examined the association between team performance perceived by coaches, coaches` basic psychological needs, motivation, and their intentions to persist in coaching. Participants were 719 coaches (80 females, M = 33.49 years, SD = 10.27, range = 18-67) of different team sports (soccer = 514; basketball = 165; volleyball = 23; handball = 14; and hockey = 3) who completed questionnaire measures at the end of the season. Structural equation modelling adjusted for sex, coaches` experience, age categories, and type of sport revealed that coaches` perceptions of team performance were positively related to their need satisfaction and negatively to their need frustration. In turn, coaches` need satisfaction was positively associated with their autonomous motivation, whereas their need frustration was positively related to controlled motivation and amotivation. Finally, coaches` autonomous motivation was a positive predictor of their intentions to persist, and conversely, coaches` amotivation was a negative predictor of their intentions to persist. We found a significant positive and indirect effect between team performance perceived by coaches and their intention to persist through their need satisfaction and autonomous motivation. These findings represent the first quantitative insight into how coach-perceived team performance could function as a new antecedent relevant to coaches` motivational processes and persistence.